Relationship between performance and vertical stiffness in triathlon running during a competition - Takahashi, K.; Nabekura, Y. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to clarify the relationship between performance and vertical stiffness of triathletes in isolated running (IR; running without a prior swim and cycling) and triathlon running (TR; running preceded by a 1.5-km swim and 40-km cycling). The mean running speed during 10-km run and the vertical stiffness in IR and TR conditions were assessed. The vertical stiffness was positively related to the running speed in both, the IR and TR conditions. The relationship between the running speed and the vertical stiffness were stronger in TR than in IR. Improvement of vertical stiffness should be important to enhance the performance in TR.